Research Progress of Carboxymethyl Galactomannan - Xiaojia BIAN; Rui LI; Xin JIA; Yongqiang CHENG (Shipin gongye ke-ji, 2022)
Galactomannan is a polysaccharide natural polymer compound, which has certain water-solubility, thickening and cross-linking, but has the shortcomings of long dispersion process and low solubility. Physical or chemical modification of galactomannan to optimize physical and chemical properties and improve product performance is the focus of current research. The anionic derivatives modified by carboxymethyl have obvious improvement in dissolution rate, water solubility, transparency and so on, and have broad application prospects. In this paper, the composition, structure and defects of galactomannan in industrial production are introduced, and the necessity of modification and the advantage of carboxymethyl modification are described. Secondly, the modification methods, characterization and application status of carboxymethyl galactomannan are summarized. The structure and rheological properties of the modified galactomannan as well as its research progress in the medical field as a sustained-release carrier are summarized. In the end, the limitations of the research status quo of carboxymethyl galactomannan and the direction of future research are summarized and prospected, in order to provide reference for expanding the application field and depth of galactomannan resources in China.